Edukasi dan Pelatihan Penyusunan Business Model Canvas (BMC) Bagi Wirausaha Pemula untuk Perencanaan Usaha Yang Inovatif - Handajani, Lilik; Hamdani Husnan, Lalu; Sokarina, Ayudia (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The rapid growth of small businesses in local communities is often not supported by adequate planning and management. Limited managerial skills, minimal entrepreneurial experience, weak financial controls, rising bad debts, and ineffective marketing strategies are among the key factors contributing to business failure among new entrepreneurs. This community service program aims to provide education and training in innovative business planning for beginner or new entrepreneurs in the West Lombok region through the application of the Business Model Canvas (BMC). The implementation of this community service program includes the delivery of materials by the community service team (facilitators), business plan preparation simulations conducted by participants, and interactive discussions between facilitators and participants. The results show improvements in participants’ knowledge, understanding, and skills in applying the BMC as a strategic business planning tool. This initiative has strengthened the capacity of new entrepreneurs to design effective strategies, seize opportunities, and mitigate risks, thereby fostering business growth and sustainability.